Substrate-dependent transport of the NADPH:protochlorophyllide oxidoreductase into isolated plastids. - Reinbothe, S (1995)
The key regulatory enzyme of chlorophyll biosynthesis in higher plants, the light-dependent NADPH:protochlorophyllide oxidoreductase (POR), is a nuclear-encoded plastid protein. Its post-translational transport into plastids is determined by its substrate. The precursor of POR (pPOR) is taken up and processed to mature size by plastids only in the presence of protochlorophyllide (Pchlide). In etioplasts, the endogenous level of Pchlide saturates the demands for pPOR translocation. During the light-induced transformation of etioplasts into chloroplasts, the Pchlide concentration declined drastically, and isolated chloroplasts rapidly lost the ability to import the precursor enzyme. The chloroplasts' import capacity for the pPOR, however, was restored when their intraplastidic level of Pchlide was raised by incubating the organelles in the dark with delta-aminolevulinic acid, a common precursor of tetrapyrroles. Additional evidence for the involvement of intraplastidic Pchlide in regulating the transport of pPOR into plastids was provided by experiments in which barley seedlings were grown under light/dark cycles. The intraplastidic Pchlide concentration in these plants underwent a diurnal fluctuation, with a minimum at the end of the day and a maximum at the end of the night period. Chloroplasts isolated at the end of the night translocated pPOR, whereas those isolated at the end of the day did not. Our results imply that the Pchlide-dependent transport of the pPOR into plastids might be part of a novel regulatory circuit by which greening plants fine tune both the enzyme and pigment levels, thereby avoiding the wasteful degradation of the imported pPOR as well as photodestruction of free Pchlide.